The formation of student’s competencies outside school (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers the problem of organizing leisure and freetime for students, and also suggests a way to improve and optimize theeducational process. There is presented the analysis of various views onthe modern education system, the problems of youth in the frameworkof educational activities and the features of the formation of relevantknowledge. Moreover, there are presented the result of a diagnostic studyon optimizing the time of summer vacation to influence the level ofmemorization, motivational sphere and student activity and to ensurethe comprehensive development of students in accordance with modernneeds.
Keywords: vacation; quality of education; motivation; recreation; competence; continuous development